Mitochondrial Toxicogenomics for Antiretroviral Management: HIV Post-exposure Prophylaxis in Uninfected Patients - Bañó, Maria; Morén, Constanza; Barroso, Sergio; Juárez, Diana Luz; Guitart-Mampel, Mariona; González-Casacuberta, Ingrid; Canto-Santos, Judith; Lozano, Ester; León, Agathe; Pedrol, Enric; Miró, Òscar; Tobías, Ester; et al. (Frontiers in Genetics, 2020)
Background: Mitochondrial genome has been used across multiple fields in research, diagnosis, and toxicogenomics. Several compounds damage mitochondrial DNA (mtDNA), including biological and therapeutic agents like the human immunodeficiency virus (HIV) but also its antiretroviral treatment, leading to adverse clinical manifestations. HIV-infected and treated patients may show impaired mitochondrial and metabolic profile, but specific contribution of viral or treatment toxicity remains elusive. The evaluation of HIV consequences without treatment interference has been performed in naïve (non-treated) patients, but assessment of treatment toxicity without viral interference is usually restricted to in vitro assays. Objective: The objective of the present study is to determine whether antiretroviral treatment without HIV interference can lead to mtDNA disturbances. We studied clinical, mitochondrial, and metabolic toxicity in non-infected healthy patients who received HIV post-exposure prophylaxis (PEP) to prevent further infection. We assessed two different PEP regimens according to their composition to ascertain if they were the cause of tolerability issues and derived toxicity. Methods: We analyzed reasons for PEP discontinuation and main secondary effects of treatment withdrawal, mtDNA content from peripheral blood mononuclear cells and metabolic profile, before and after 28 days of PEP, in 23 patients classified depending on PEP composition: one protease inhibitor (PI) plus Zidovudine/Lamivudine (PI plus AZT + 3TC; n = 9) or PI plus Tenofovir/Emtricitabine (PI plus TDF + FTC; n = 14). Results: Zidovudine-containing-regimens showed an increased risk for drug discontinuation (RR = 9.33; 95% CI = 1.34–65.23) due to adverse effects of medication related to gastrointestinal complications. In the absence of metabolic disturbances, 4-week PEP containing PI plus AZT + 3TC led to higher mitochondrial toxicity (−17.9 ± 25.8 decrease in mtDNA/nDNA levels) than PI plus TDF + FTC (which increased by 43.2 ± 24.3 units mtDNA/nDNA; p < 0.05 between groups). MtDNA changes showed a significant and negative correlation with baseline alanine transaminase levels (p < 0.05), suggesting that a proper hepatic function may protect from antiretroviral toxicity. Conclusions: In absence of HIV infection, preventive short antiretroviral treatment can cause secondary effects responsible for treatment discontinuation and subclinical mitochondrial damage, especially pyrimidine analogs such as AZT, which still rank as the alternative option and first choice in certain cohorts for PEP. Forthcoming efforts should be focused on launching new strategies with safer clinical and mitotoxic profile.